“Fire burns matter: A case-control study of severe accidental burns in pediatric patients“ - Rojas-Contreras, Christian (2022)
“Objective: We aimed to identify factors associated with severe accidental burns in patients ≤12 years old. Materials and methods: We conducted a matched case-control study, in which we retrospectively reviewed the medical records of children treated in a single institution from 2014-2016. We classified the cases (patients with severe burns) and controls (patients with non-severe burns) according to the criteria of the American Burn Association. We used multivariate conditional logistic regression analysis to identify the relationship between the etiology of burns and their severity. Results: We reviewed 180 cases and 90 controls. The most common etiology of burns was boiling water in both cases (65.6%) and controls (83.3%). Most burns occurred inside the home (84.1%) and in the afternoon (37.4%). Multivariate analysis identified that severe burns were mainly due to exposure to fire (odds ratio [OR]: 3.22, 95% confidence interval [CI]: 1.53-6.81). Similarly, these patients were more likely to live in a rural area (OR: 2.96, 95% CI: 1.17-6.19). Conclusions: In pediatric patients ≤12 years of age severe accidental burns are more likely to be caused by fire compared to boiling water. Public health interventions should focus on populations located in rural areas.“